The Attitude and Actions of Leaders in Developing an Inclusive School - Miltenienė , Lina; Valuckienė, Jūratė; Damkuvienė, Milda; Balčiūnas, Sigitas; Petukienė, Evandželina; Bugenytė, Meda (Special Education, 2022)
usive education, chosen by a school. The implementation of the project in Lithuania is supported by the programme “I choose to teach – for school change!”, which aims to increase inclusive education as a focus on each child and the child’s continuous learning progress. The article presents interviews with 14 principals of Lithuanian general education schools, who participated in the first stage of the programme “I choose to teach – for school change!”. The interviews were aimed at finding out school leaders’ attitudes towards inclusive education, their actions of planning and managing transformational processes taking place in school while strengthening inclusive education. Applying the method of inductive qualitative content analysis, four themes revealing the diversity of school leaders’ attitudes and actions in creating the inclusive school were distinguished: 1) the deconstruction of the phenomenon of inclusion, singling out the categories of acknowledgment of individuality and equal opportunities, every child’s progress and participation, and the development of general competencies; 2) personal readiness for strengthening inclusion, where the elements of internalization of the sense of change and acknowledgment of challenges of change have come to light; 3) leadership projections manifesting themselves through the “declaration” of value priorities by personal example, initiatives supporting and inspiring teachers; and 4) reorganisation of organizational structures in creating and formalising internal procedures and agreements, the collegial learning system and in making decisions that mobilise various types of resources.